Clinical and Radiographic Evaluation of Patients Treated with ITI Dental Implants and Evaluation of their Satisfaction - M Rismanchian; A Fazel (Isfahan University of Medical Sciences, 2007)
Introduction: Dental implants are used increasingly in educational and clinical centers due to their ability to provide esthetic and function in patients. The aim of this study was to evaluate patients treated with ITI Dental implants clinically and radiographically, and also evaluate their satisfaction from esthetic and practical point of view.Methods and Materials: In this analytical descriptive retrospective study, 318 ITI Dental implants were placed for 107 patients (male and females). Implants were evaluated clinically and radiographically after two years of loading. Soft and hard tissue supporting implants were also evaluated. Patients' satisfaction was evaluated from esthetic and prosthetic functional aspect via questionnaires. The data was analyzed with ANOVA and Mann-Whitney tests using SPSS software.Results: From total of 318 placed ITI dental implants, 3 implants failed before loading and 2 implants after loading. Therefore survival rate was 99% up to loading period and after 2-7 years of loading was 98/4%. Soft and hard tissue health was within predetermined standard limits. More than 90% of patients were satisfied with different aspects of their treatment.Conclusion: Results of this study confirm the accuracy of clinicians and the ability of the system being used. In case of correct diagnosis and treatment ITI dental implants can be used as favorable treatment option for complete and partial edentulous patients with success rate of more than 98.4%. Key word: Dental health education, health knowledge, primary school children